Spectral investigation of the diffuse-to-direct solar beam irradiances ratio (UV-VIS) in the urban Athens atmosphere - Jacovides, C.P.; Kaltsounides, N.A.; H. A. Flocas; Asimakopoulos, D.N. (Meteorology and Atmospheric Physics, 2009)
This study explores the influence of air gaseous pollutants-aerosols and solar zenith angle (SZA) on the spectral diffuse-to-direct beam Edλ/Ebλ irradiances ratio. It does so using ground-based spectroradiometric measurements taken over the Athens atmosphere during May 1995. It was found that the spectral Edλ/Ebλ ratio decreases rapidly with increasing wavelength and regression curves of the form EEdλ/Ebλ = aλ-b fitted the experimental data. These curves are strongly modified by aerosols-air pollutants, aerosol optical properties, and SZA. The log-log plot of Edλ/Ebλ versus λ reveals a significant departure from linearity, which is likely to be associated with aerosol physical properties and SZA effects. The effect of atmospheric turbidity, as expressed through the aerosol optical at 500 nm and SZA on the spectral Edλ/ Ebλ ratio, is investigated in detail for two discernible atmospheric conditions observed in the urban Athens atmosphere. The first case includes different atmospheric turbidity levels under the same SZA, while the second corresponds to different SZA values under the same turbidity levels. It was found that the correlation between Edλ/Ebλ and spectral aerosol optical depth can be a useful tool in determining the aerosol optical properties and aerosol types composition. © Springer-Verlag 2009.
Keywords: aerosol; aerosol property; Athens [Attica]; atmospheric pollution; Attica; Eurasia; Europe; Greece; optical depth; Southern Europe; spectral analysis; Turbidity; urban atmosphere